INVESTIGATING THE EFFECT OF DRAMA AS TEACHING TECHNIQUE ON GRADE EIGHT STUDENTS’ VOCABULARY ACQUISITION - Deddy Suezdi; Denada NA (Lingua, 2017)
This research entitled “Investigating The Effect of Drama as Teaching Technique on Grade Eight Students’ Vocabulary Acquisition at MTs Assyairiyah Attahiriyah Jakarta” principally aims to investigate whether or not drama technique significantly affects students’ vocabulary acquisition. The research samples were taken using cluster random sampling, with the total number of samples being 60 students. The location of this research was MTs Assyairiyah Attahiriyah Jakarta. The research methodology adopted was quasi-experiment method, with the research design being post test only control group design. To collect the data, the students were given the objective test, numbering 30 items. The research data were analyzed descriptively and inferentially. The findings indicated that there was significant difference of post-test score between the students who received drama technique and students who did not receive drama technique. It can be seen from the data analysis using ANOVA that showed Fobserved (90.988) is higher than the critical value of Ftable (at the significant level of 0.05 and df = 1/84), namely 3.96. it means that drama technique has significant effect on students’ vocabulary acquisition.